2013
DOI: 10.1371/journal.pone.0082712
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Photosynthetic Performance of Coffea spp. under Long-Term Enhanced [CO2]

Abstract: Coffee is one of the world’s most traded agricultural products. Modeling studies have predicted that climate change will have a strong impact on the suitability of current cultivation areas, but these studies have not anticipated possible mitigating effects of the elevated atmospheric [CO2] because no information exists for the coffee plant. Potted plants from two genotypes of Coffea arabica and one of C. canephora were grown under controlled conditions of irradiance (800 μmol m-2 s-1), RH (75%) and 380 or 700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
118
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(135 citation statements)
references
References 68 publications
11
118
0
1
Order By: Relevance
“…Although the g s values, integrated over the course of the day, could be decreased by elevated [CO 2 ] under winter conditions in Obatã, our daily averaged g s values were clearly unaffected by the treatments when gas exchange is at its maximum during the growing season (Silva et al 2004). Ramalho et al (2013) observed that g s was also unaffected by the high [CO 2 ] treatment. Saldanha et al (2013) were also unable to detect any changes in stomatal index and density and g s in somatic embryogenesis-derived coffee plantlets grown at 360 or 1000 μmol CO 2 mol −1 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although the g s values, integrated over the course of the day, could be decreased by elevated [CO 2 ] under winter conditions in Obatã, our daily averaged g s values were clearly unaffected by the treatments when gas exchange is at its maximum during the growing season (Silva et al 2004). Ramalho et al (2013) observed that g s was also unaffected by the high [CO 2 ] treatment. Saldanha et al (2013) were also unable to detect any changes in stomatal index and density and g s in somatic embryogenesis-derived coffee plantlets grown at 360 or 1000 μmol CO 2 mol −1 .…”
Section: Discussionmentioning
confidence: 97%
“…These results suggest that photosynthetic downregulation is unlikely to have occurred under our experimental conditions. Notably, Ramalho et al (2013) reported compelling evidence demonstrating lack of downregulation in response to elevated [CO 2 ] (700 μmol CO 2 mol −1 ) in three coffee cultivars grown in large pots in growth chambers for 1 year. Taken together, this information suggests that coffee can sustain relatively high photosynthetic rates under a scenario of increasing atmospheric [CO 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the interest in C. canephora is growing, due to an increasing consumption of instant coffee and blends, to some uncertainty of C. arabica production related to changing climate conditions (BICC, 2014), and because it shows a better ability to tolerate some climatic events when compared to C. arabica (DaMatta and Ramalho, 2006;Ramalho et al, 2013b;Martins et al, 2014). The increased climate tolerance is related to the evolutionary history of the species.…”
Section: Mitigation and Adaptationmentioning
confidence: 99%
“…Those included severe losses of traditional suitable areas (Assad et al, 2004), significant yield reductions (Gay et al, 2006), extinction of wild populations of C. arabica (Davis et al, 2012), and a strong vulnerability in agricultural, social and economic aspects related to this culture (Baca et al, 2014). Still, future studies must consider the possible mitigating effects of the enhanced atmospheric [CO 2 ] on the adverse impacts of elevated temperatures that have begun to be grasped only recently (Ramalho et al, 2013b;Martins et al, 2014). Furthermore, it was reported that some coffee genotypes are particularly able to adapt to harsh environmental constraints, e.g., temperature, irradiance, water and nutrients (Ramalho et al, 1999;DaMatta and Ramalho, 2006;Fortunato et al, 2010;Batista-Santos et al, 2011;Cavatte et al, 2012;Ramalho et al, 2013a;Scotti-Campos et al, 2014), what further emphasis the need to reinforce such biophysical studies.…”
Section: Introductionmentioning
confidence: 99%